Internal
problem
ID
[6256]
Book
:
Fundamentals
of
Differential
Equations.
By
Nagle,
Saff
and
Snider.
9th
edition.
Boston.
Pearson
2018.
Section
:
Chapter
2,
First
order
differential
equations.
Section
2.2,
Separable
Equations.
Exercises.
page
46
Problem
number
:
1
Date
solved
:
Monday, January 27, 2025 at 01:50:13 PM
CAS
classification
:
[[_homogeneous, `class C`], _dAlembert]
Time used: 0.017 (sec). Leaf size: 25
Time used: 37.820 (sec). Leaf size: 541
\begin{align*}
y(x)\to -2 \arccos \left (\frac {(x+c_1) \sin \left (\frac {x}{2}\right )-(x-2+c_1) \cos \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2+2 (-1+c_1) x+2+c_1{}^2-2 c_1}}\right ) \\
y(x)\to 2 \arccos \left (\frac {(x+c_1) \sin \left (\frac {x}{2}\right )-(x-2+c_1) \cos \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2+2 (-1+c_1) x+2+c_1{}^2-2 c_1}}\right ) \\
y(x)\to -2 \arccos \left (\frac {(x-2+c_1) \cos \left (\frac {x}{2}\right )-(x+c_1) \sin \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2+2 (-1+c_1) x+2+c_1{}^2-2 c_1}}\right ) \\
y(x)\to 2 \arccos \left (\frac {(x-2+c_1) \cos \left (\frac {x}{2}\right )-(x+c_1) \sin \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2+2 (-1+c_1) x+2+c_1{}^2-2 c_1}}\right ) \\
y(x)\to -2 \arccos \left (\frac {\cos \left (\frac {x}{2}\right )-\sin \left (\frac {x}{2}\right )}{\sqrt {2}}\right ) \\
y(x)\to 2 \arccos \left (\frac {\cos \left (\frac {x}{2}\right )-\sin \left (\frac {x}{2}\right )}{\sqrt {2}}\right ) \\
y(x)\to -2 \arccos \left (\frac {\sin \left (\frac {x}{2}\right )-\cos \left (\frac {x}{2}\right )}{\sqrt {2}}\right ) \\
y(x)\to 2 \arccos \left (\frac {\sin \left (\frac {x}{2}\right )-\cos \left (\frac {x}{2}\right )}{\sqrt {2}}\right ) \\
y(x)\to -2 \arccos \left (\frac {(x-2) \cos \left (\frac {x}{2}\right )-x \sin \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2-2 x+2}}\right ) \\
y(x)\to 2 \arccos \left (\frac {(x-2) \cos \left (\frac {x}{2}\right )-x \sin \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2-2 x+2}}\right ) \\
y(x)\to -2 \arccos \left (\frac {x \sin \left (\frac {x}{2}\right )-(x-2) \cos \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2-2 x+2}}\right ) \\
y(x)\to 2 \arccos \left (\frac {x \sin \left (\frac {x}{2}\right )-(x-2) \cos \left (\frac {x}{2}\right )}{\sqrt {2} \sqrt {x^2-2 x+2}}\right ) \\
\end{align*}